Evaluasi Sediaan Krim Ekstrak Etanol Daun Tapak Dara (Catharanthus roseus L.) Sebagai Tabir Surya dalam Menghambat Pembentukan Eritema - Akhmad Al-bari; Romadhiyana Kisno Saputri; Sovia Roikhatul Jannah (Pelantar Press, 2023)
Sunlight is composed of visible and ultraviolet light, but only 10% of the UV can penetrate the Earth's atmosphere. Exposure to UV-B on human skin can result in sunburn and erythema. To avoid skin damage from UV, sunscreens containing oxybenzone and octinoxate compounds are used. However, these compounds can have adverse effects on the skin, so finding a more natural alternative is essential. Phenolic compounds and flavonoids, which are found in plants, are believed to serve as natural sunscreens and protect the skin from erythema caused by UV exposure. The objective of this study was to assess the efficacy of tapak daura leaf extract cream as a natural sunscreen to prevent erythema in mice. The extract was made using the maceration method with 96% ethanol in a 1:4 ratio. Three sunscreen cream formulations were created using 1%, 1.5%, and 3% concentrations of tapak daura leaf extract, respectively. Formulation F0 did not include the extract. The creams were then tested on mouse skin and exposed to UV-B for eight hours. The results demonstrated that tapak daura leaf extract sunscreen cream could protect against UV-B rays by reducing the number of erythema spots in the F3 group from 6.3 to only two.